KOMPARASI PENDIDIKAN ISLAM DI INDONESIA - Dede Misbahul Alam; Nurhasanah; Nina Rahmawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islamic education in Indonesia has developed in various forms and models influenced by social, cultural, political, and national education policy dynamics. This diversity has given rise to differences in the characteristics of Islamic education provided by formal, non-formal, and informal institutions. This study aims to conduct a comparative analysis of the Islamic education system in Indonesia by examining aspects of educational objectives, curriculum, learning methods, and its contribution to the formation of students' personalities. The method used is a literature study by analyzing various relevant scientific sources, including books, journals, and educational policy documents. The results of the study show that Islamic education in Indonesia has advantages in strengthening moral and spiritual values, but still faces challenges in integrating modern science and technology. Differences in approach between Islamic boarding schools, madrasas, and Islamic public schools show variations in educational orientation and learning outcomes. The conclusion of this study emphasizes that strengthening the synergy between Islamic education models is necessary to create an adaptive, competitive education system that remains based on Islamic values.